2022
DOI: 10.3390/ani12050587
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Volume of Injectate Using a Dose Regimen Based on Occipito-Coccygeal Spinal Length (OCL): Randomized Clinical Study Comparing Different Ropivacaine Concentrations, with or without Morphine, in Bitches Undergoing Total Unilateral Mastectomy

Abstract: A prospective, randomized clinical trial was designed to compare four epidural treatments in dogs undergoing total unilateral mastectomy. The epidural volume of injectate was based on the individual occipito-coccygeal length (OCL) aiming to reach the first thoracic vertebra (T1). The first ten dogs were allocated in a control group (C) and did not receive epidural treatment. Subsequently, forty dogs were randomly allocated in four groups of ten: epidural ropivacaine 0.5% (R0.5%); morphine 0.1 mg kg−1 plus ropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In addition, in this study, both HR and FE'Iso were significantly lower in group ROPI than in group CNT. These data are well reported in veterinary literature and confirm the advantages of locoregional anaesthesia, such as the sparing effect on inhalant anaesthetic drugs and a more stable anaesthetic plane during surgery, in comparison with a group receiving systemic analgesia (Grubb & Lobprise 2020;Tayari et al 2022). Innervation of epaxial muscles, vertebral laminae and facet joints in dogs is provided by the medial branches of the DRSN (Forsythe & Ghoshal 1984;Evans & de Lahunta 2013).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, in this study, both HR and FE'Iso were significantly lower in group ROPI than in group CNT. These data are well reported in veterinary literature and confirm the advantages of locoregional anaesthesia, such as the sparing effect on inhalant anaesthetic drugs and a more stable anaesthetic plane during surgery, in comparison with a group receiving systemic analgesia (Grubb & Lobprise 2020;Tayari et al 2022). Innervation of epaxial muscles, vertebral laminae and facet joints in dogs is provided by the medial branches of the DRSN (Forsythe & Ghoshal 1984;Evans & de Lahunta 2013).…”
Section: Discussionsupporting
confidence: 68%
“…This finding may suggest that the QLB LQL-T with ropivacaine 0.5% and 0.33% provided a similar anesthetic and analgesic plane to a systemic fentanyl-based analgesic protocol. However, although the difference was not statistically significant, dogs in groups receiving QLB LQL-T suffered less cardiovascular complications than dogs in group No-QLB, as reported in the literature [7,8]. Nine out of sixteen dogs required intraoperative rescue fentanyl in groups QLB during S 1 , S 2 , and S 3 .…”
Section: Discussionmentioning
confidence: 60%
“…To permit such a prompt discharge, effective perioperative analgesia is essential to reduce the occurrence of uncontrolled post-surgery stress responses, including immunosuppression, overstimulation of the sympathetic nervous system, and anorexia [6]. Locoregional anesthesia (LRA) can provide a more stable anesthetic plane due to the sparing effect on inhalant anesthetic drugs and a reduction in the use of intra-and postoperative opioids [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only 37% of the dogs in the LS and 29% dogs in the SC group needed rescue opioids in the postoperative period, with no difference between the epidural techniques. Cardiovascular depression requiring treatment was observed in several dogs before the epidural injection (28). The dogs in which the epidural injection triggered cardiovascular depression were fewer (18), with no difference between the groups.…”
Section: Discussionmentioning
confidence: 95%
“…The same might applies to ropivacaine, and in general to local anesthetics. Indeed Campoy et al ( 28 ), suggested that once the nerves are blocked, a greater concentration of local anesthetic serves to increase the intensity and the duration of effect.…”
Section: Discussionmentioning
confidence: 99%